Two New Acidic Diterpenoids from the Heartwood of Pinus massonianaLamb. Issue 8 (August 2014) - Abd. Mohamed, H.; Hsieh, Chin‐Lin; Hsu, Chin; Kuo, Ching‐Chuan; Chang, Hsuan‐Shuo; Lee, Ching‐Kuo; Lee, Tzon‐Huei; Wu, Jin‐Bin; Chang, Chi‐I; Kuo, Yueh‐Hsiung
Abstract A new abietane diterpene, named abietopinoic acid, and a new podocarpane diterpene, named podopinoic acid, were isolated from the acetone extract of the heartwood of Pinus massoniana. Their structures were established as 12‐hydroxy‐7‐oxoabieta‐8, 11, 13‐trien‐18‐oic acid (1) and 13‐hydroxy‐7‐oxopodocarpane (2) by means of spectroscopic analyses including 2D‐NMR. To the best of our knowledge, this is the second report of a podocarpa‐8, 11, 13‐trien‐18‐oic acid diterpene, isolated from the genus Pinus.